Program Edukasi Ketahanan Pangan dan Mengurangi Sampah pada Siswa SDN 01 Sawah Baru - Moningka, Clara; Tienovani Simanjuntak, Maria Jane (Devotion : Jurnal Pengabdian Psikologi, 2024)
This community service program is carried out for students at Elementary School 01 Sawah Baru who do not yet know about a sustainable environment. This program is carried out with the aim of shaping pro-environmental behavior, including understanding food security and reducing waste. Psychoeducation was carried out from August 2023 to March 2024 using lecture and action learning methods. To determine the level of students' understanding, a pre-test and post-test were carried out. The results of statistical calculations show that there are differences in students' knowledge and understanding after participating in psychoeducation. The psychoeducation carried out is effective, which is shown by changes in the understanding and behavior of students at SDN 01 Sawah Baru.